COMPARISON OF MEAN BIRTH WEIGHT OF NEONATES BORN TO FEMALES HAVING GESTATIONAL DIABETES ON METFORMIN VERSUS INSULIN - Siddique, Nasir; Shakil, Muhammad; Anwar, Seemab; Mehmood, Nimra; Ullah, Muhammad Ikram (Journal of Postgraduate Medical Institute, 2018)
Objective: To compare the mean birth weight of neonates born to women having gestational diabetes treated with oral metformin versus insulin. Methodology: In this study, 360 females with gestational diabetes (GDM) were selected. The subjects were randomly divided into two equal groups. In group A, during first week of trimester, metformin was administrated in 750 mg once daily dose, two times per day during second week and thrice daily from the third week onwards. In group B, long-acting insulin was used to normalize fasting, and rapid-acting insulin was used to normalize postprandial glucose concentrations. Patients were followed till delivery and birth weight of baby was noted. All this information was recorded on proforma. Data was analyzed using SPSS-17 and t-test was applied to compare the mean birth weight in both groups. P value <0.05 was considered as statistically significant. Results: The mean birth weight was 3459.9 ±238.9 grams. In metformin group, the mean neonatal birth weight was 3557.02 ±232.34 grams. In insulin group, the mean neonatal birth weight was 3362.79 ±203.72grams. There was significant difference between both groups and insulin group showed less birth weight as compared to metformin group (p <0.05). Conclusion: Insulin was more beneficial in maintaining weight of fetus as compared to metformin in patients with gestational diabetes mellitus.